2022
DOI: 10.1007/s11356-022-24748-1
|View full text |Cite
|
Sign up to set email alerts
|

Can digital finance reduce carbon emission intensity? A perspective based on factor allocation distortions: evidence from Chinese cities

Abstract: The world is facing the challenges of climate change and energy structure adjustments. The role of digital nance, a new branch of business that combines digital technology and traditional nancial products, in reducing global carbon emissions needs to be studied. This paper uses panel data on 280 cities in China from 2011 to 2019 to empirically examine the e cacy of digital nance for governing carbon emission reductions and the mechanism by which it does so. The results show that: 1. digital nance can facilitat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Labor supply in these industries has less impact on the financial sector, and it is difficult to affect the level of development of digital financial inclusion directly; digital financial inclusion and the overwork of migrant workers between the reverse causality are difficult to establish. But even so, considering that the possibility of endogeneity problems caused by omitted variables still exists, to ensure the rigor of study, this paper refers to the study of Yang ( 43 ) and selects the level of Internet development as an instrumental variable of digital financial inclusion, measured by the number of Internet access users in each prefecture-level city in 2017 (denoted as IV). In addition, this paper also adds the lagged one period of the digital financial inclusion index as the second instrumental variable (denoted as IV2), and the lagged one period of the digital financial inclusion index is directly related to the digital financial inclusion index without directly affecting the willingness to stay of the migrant workers.…”
Section: Resultsmentioning
confidence: 99%
“…Labor supply in these industries has less impact on the financial sector, and it is difficult to affect the level of development of digital financial inclusion directly; digital financial inclusion and the overwork of migrant workers between the reverse causality are difficult to establish. But even so, considering that the possibility of endogeneity problems caused by omitted variables still exists, to ensure the rigor of study, this paper refers to the study of Yang ( 43 ) and selects the level of Internet development as an instrumental variable of digital financial inclusion, measured by the number of Internet access users in each prefecture-level city in 2017 (denoted as IV). In addition, this paper also adds the lagged one period of the digital financial inclusion index as the second instrumental variable (denoted as IV2), and the lagged one period of the digital financial inclusion index is directly related to the digital financial inclusion index without directly affecting the willingness to stay of the migrant workers.…”
Section: Resultsmentioning
confidence: 99%
“…On the one hand, digital inclusive finance is based on digital platforms that digitize offline enterprises. According to transaction cost theory, online financial services significantly reduce high transaction costs and resource consumption resulting from transaction uncertainty and high transaction frequency (Yang et al, 2022), thereby promoting carbon emissions reduction. On the other hand, environmental service platforms in digital finance, such as "Ant Forest," have increased public engagement in environmental activities, motivating individuals to adopt lowcarbon lifestyles (Sun et al, 2021).…”
Section: Theoretical Analysis and Research Hypotheses 21 Carbon Emiss...mentioning
confidence: 99%
“…From the perspective of distorted element configuration, Yang conducted an empirical test regarding the role and working mechanism of DF in carbon emission reduction based on the panel data of 280 cities in China from 2011 to 2019. The results indicated that DF facilitates rational resource allocation and reduction in carbon emissions [26]. From the perspective of capital bias towards technological advances, Li analyzed the impacts of DF on low-carbon energy transformation based on the panel data of 283 cities in China, and it was found that DF can improve carbon total factor productivity and the proportion of clean energy in total energy consumption, exhibiting positive impacts on low-carbon energy transformation [27].…”
Section: Introductionmentioning
confidence: 99%